2018
DOI: 10.16997/jdd.291
|View full text |Cite
|
Sign up to set email alerts
|

The Instrumental Value of Deliberative Democracy – Or, do we have Good Reasons to be Deliberative Democrats?

Abstract: Though commanding a prominent role in political theory, deliberative democracy has also become a mainstay of myriad other research traditions in recent years. This diffusion has been propelled along by the notion that deliberation, properly conceived and enacted, generates many beneficial outcomes. This article has three goals geared toward understanding whether these instrumental benefits provide us with good reasons-beyond intrinsic ones-to be deliberative democrats. First, the proclaimed instrumental benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…My claim is not that empathetic understanding is easy or that it will naturally result from discussing politics with people from diverse perspectives. 20 Rather, I claim that mutual understanding ought to be a conscious goal of democratic deliberation and (more controversially) that it should often take priority over other deliberative 19 Mendelberg and Oleske (2000) found that discussion did not produce greater tolerance for opposing views, but Kuyper (2018) argues that this work suffers from a methodological bias, namely, it was reliant upon participants' self-assessment for measures of empathy. Recent studies that rely upon more objective measures (e.g., Siu 2008) are more promising.…”
Section: Empirical Supportmentioning
confidence: 99%
“…My claim is not that empathetic understanding is easy or that it will naturally result from discussing politics with people from diverse perspectives. 20 Rather, I claim that mutual understanding ought to be a conscious goal of democratic deliberation and (more controversially) that it should often take priority over other deliberative 19 Mendelberg and Oleske (2000) found that discussion did not produce greater tolerance for opposing views, but Kuyper (2018) argues that this work suffers from a methodological bias, namely, it was reliant upon participants' self-assessment for measures of empathy. Recent studies that rely upon more objective measures (e.g., Siu 2008) are more promising.…”
Section: Empirical Supportmentioning
confidence: 99%
“…In addition to having a good understanding of citizens' dissatisfaction with the status quo, there is also evidence that it is possible to meet expectations and close the Arnstein gap. Previous research on the case studies used later in this article analyzed a deliberative democracy intervention [79] aimed specifically at increasing the public participation level to "partnership" [55]. The Arnstein gap between expectation and reality closed by two-thirds in response to this intervention.…”
Section: Public Participation As a Way Of Building Political Trustmentioning
confidence: 99%
“…An even more complicated question is why we should consider deliberation the foundation of democratic legitimacy. Although deliberative democracy is often justified on intrinsic, deontological grounds (Gutmann & Thompson, 1996;Habermas, 1996), a number of theorists have argued that it also requires an instrumental justification, showing that it tends to produce beneficial outcomes (Kuyper, 2018;Martí, 2006). However, the claim that deliberation produces beneficial outcomes raises a new question, which has perhaps been insufficiently articulated in earlier work, and which has no single answer: beneficial relative to what alternative?…”
Section: Two Challenges In Deliberative Democracymentioning
confidence: 99%